Analysis of Examination of Evidence Through the Scientific Crime Investigation Method in the Disclosure of Homicide Crimes - Hefa Ruspita; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Risdalina Risdalina (International Journal Labs, 2022)
Background: Law enforcement is one of the efforts to create order, security, and peace in the community, especially enforcement after violations of the law. Objective: This study aims to find out and analyze the strengthening of evidence through scientific crime investigation in homicide crimes. As well as knowing and analyzing the advantages and disadvantages of using the scientific crime investigation method in crime scene processing carried out by the forensic laboratory. Methods: This research belongs to the normative type of research. So that it can be known that the scientific crime investigation method is used in proving the crime of forensic murder. Result: Article 184 paragraph (1) of the Criminal Procedure Code has restrictively regulated valid evidence according to the law. Apart from the aforesaid evidence, it is not justifiable to be used to prove the wrongs committed by the accused. Judges, public prosecutors, defendants, and legal counsel, are limited and bound to use evidence by the rules of criminal procedure only. Evidence using evidence other than the evidence provided in Article 184 paragraph (1) has no binding evidentiary force value. Conclusion: Based on the explanation above, it can be concluded that the scientific crime investigation method is used in proving the crime of forensic murder